Required transition from research to clinical application: Report on the 4D treatment planning workshops 2014 and 2015. Issue 7 (July 2016) - Knopf, Antje-Christin; Stützer, Kristin; Richter, Christian; Rucinski, Antoni; da Silva, Joakim; Phillips, Justin; Engelsman, Martijn; Shimizu, Shinichi; Werner, Rene; Jakobi, Annika; Göksel, Orçun; Zhang, Ye; et al.
Highlights: We summarize the outcome of two 4D treatment planning workshops [4DWS]. Topics include time resolved imaging, motion modelling, 4D TP and 4D dosimetry. We review recent literature on advanced radiotherapy approaches for moving targets. We identify upcoming challenges and suggest focus point for future research. Abstract: Since 2009, a 4D treatment planning workshop has taken place annually, gathering researchers working on the treatment of moving targets, mainly with scanned ion beams. Topics discussed during the workshops range from problems of time resolved imaging, the challenges of motion modelling, the implementation of 4D capabilities for treatment planning, up to different aspects related to 4D dosimetry and treatment verification. This report gives an overview on topics discussed at the 4D workshops in 2014 and 2015. It summarizes recent findings, developments and challenges in the field and discusses the relevant literature of the recent years. The report is structured in three parts pointing out developments in the context of understanding moving geometries, of treating moving targets and of 4D quality assurance (QA) and 4D dosimetry. The community represented at the 4D workshops agrees that research in the context of treating moving targets with scanned ion beams faces a crucial phase of clinical translation. In the coming years it will be important to define standards for motion monitoring, to establish 4D treatment planning guidelines and to develop 4D QA tools. These basic requirements for the clinical application of scanned ion beams to moving targets could e.g. be determined by a dedicated ESTRO task group. Besides reviewing recent research results and pointing out urgent needs when treating moving targets with scanned ion beams, the report also gives an outlook on the upcoming 4D workshop organized at the University Medical Center Groningen (UMCG) in the Netherlands at the end of 2016.